2014
DOI: 10.1021/tx5000552
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Effects of Benzene, Toluene, Ethylbenzene, and Xylenes (BTEX) on Lung Carcinoma Cells via a Hanging Drop Air Exposure System

Abstract: A recently developed hanging drop air exposure system for toxicity studies of volatile chemicals was applied to evaluate the cell viability of lung carcinoma A549 cells after 1 and 24 h of exposure to benzene, toluene, ethylbenzene, and xylenes (BTEX) as individual compounds and as mixtures of four or six components. The cellular chemical concentrations causing 50% reduction of cell viability (EC50) were calculated using a mass balance model and came to 17, 12, 11, 9, 4, and 4 mmol/kg cell dry weight for benze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…They are carcinogenic species and considered as some of the most hazardous pollutants among VOCs [29]. Acute exposure to xylene isomers and toluene, typically found in gasoline, has been associated with skin, eye irritation, and effects on the respiratory system [30]. The constant and chronic exposure to small amounts of these solvents (200 ppm or greater) in the ambient or at home with common products such as adhesives and solvents for paints is associated with various adverse health effects [27,31].…”
Section: Introductionmentioning
confidence: 99%
“…They are carcinogenic species and considered as some of the most hazardous pollutants among VOCs [29]. Acute exposure to xylene isomers and toluene, typically found in gasoline, has been associated with skin, eye irritation, and effects on the respiratory system [30]. The constant and chronic exposure to small amounts of these solvents (200 ppm or greater) in the ambient or at home with common products such as adhesives and solvents for paints is associated with various adverse health effects [27,31].…”
Section: Introductionmentioning
confidence: 99%
“…The test results are normally based on the nominal concentration of a test chemical added to the culture medium at the start of the test. However, several studies have found that volatile and/or hydrophobic chemicals evaporate from wells, [1][2][3][4] cross over to adjacent wells, 5 sorb to microtiter plates, 1,2,6,7 and sorb to medium constituents. 1,2,6,8 Therefore, the actual exposure of the cells to the test substances is often not known and decreases with time, which can lead to reduced toxicity and assay sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…BTEX has been identified as potential groundwater pollutants, which cause deleterious effects on organisms, including humans (Chen et al 2008;Li et al 2013;Lim et al 2014;Liu et al 2014). Our histological findings demonstrated obvious alterations in the progression of oogenesis in E. johanssoni with BTEX treatment of 25 µg L −1 for 26 days.…”
Section: Discussionmentioning
confidence: 99%